Volume fraction and location of voids and gaps in ultraconservative restorations by X-ray computed micro-tomography - Panagiotis Lagouvardos; Nick Nikolinakos; Constantine Oulis (Wolters Kluwer Medknow Publications, 2015)
Background: Volume fraction (Vf) and location of internal voids and gaps in relation to material type and cavity dimensions in ultraconservative restorations were investigated in this study. Materials and Methods: Forty-eight round cavities of 1.3 mm mean diameter and 2.6 mm mean depth were made on buccal and lingual surfaces of recently extracted human teeth. These were filled and thermocycled with two low viscosity composites (AeliteFlo LV [AF], PermaFlo [PF]), one high viscosity composite (Aelite aesthetic enamel [AA]) and one glass-ionomer (GCFuji IX GP). X-ray microtomography, following a specific procedure, was applied to all cavities before and after their restoration, using SkyScan-1072 microtomographer. Vf percent (Vf%) and location of voids and gaps were recorded and analysed statistically at a = 0.05. Kruskal-Wallis nonparametric analysis of variance, post-hoc analysis, Mann-Whitney test, Spearman's correlation analysis were used to analyze data. Results: Cavities filled with AF and PF showed significantly lower V f % of voids and gaps than all other restorations (P < 0.05). Only for the cavities filled with AA, cavity width and depth was significantly correlated with V f % (P < 0.05). 50-75% of the filled cavities contained internal voids regardless of the restorative material (P > 0.05). The proportion of cavities with gaps at the bottom and side walls was lower in those filled with AF and PF (P < 0.05). Conclusion: Cavities filled with low viscosity composites presented the lowest amount of internal voids and gaps. Glass-ionomer and high viscosity composite restorative materials showed the highest amount of interfacial gaps. Only in the high viscosity composite restorations the amount of voids and gaps correlated with the cavity depth, width and volume.